sarA-Dependent Antibiofilm Activity of Thymol Enhances the Antibacterial Efficacy of Rifampicin Against Staphylococcus aureus - Valliammai, Alaguvel; Selvaraj, Anthonymuthu; Yuvashree, Udayakumar; Aravindraja, Chairmandurai; Karutha Pandian, Shunmugiah (Frontiers in Microbiology, 2020)
Methicillin-resistant Staphylococcus aureus (MRSA) is a serious human pathogen which has been listed as high priority multi drug resistance pathogen by the World Health Organization (WHO). Persistent MRSA infections are often associated with biofilm formation and resistant to conventional antimicrobial therapy. Inhibiting the surface adherence and virulence of the bacterium is the current alternative approach without affecting growth to reduce the possibility of resistance development. Though numerous antibiofilm agents have been identified, their mode of action remains unclear. Combining two drugs with different mode of action will improve the efficiency of the treatment strategy against MRSA. The present study was aimed to decipher the molecular mechanism underlying the antibiofilm activity of thymol against MRSA and assess the ability of thymol to improve the antibacterial activity of rifampicin. Thymol significantly inhibited 88% of MRSA biofilm formation at 100 µg/mL and reduced the surface adherence of MRSA on glass, stainless steel and titanium surface coated with human plasma as evidenced by microscopic analyses. qPCR analysis of global virulence regulatory genes and biofilm assay with S. aureus wild type, ∆sarA and ∆agr strains revealed the sarA mediated antibiofilm activity of thymol and inhibition of sarA controlled virulence factors. Congo red assay and erythrocyte lysis assay further confirmed the reduction in polysaccharide intracellular adhesin (PIA) and hemolysin. Importantly, thymol enhanced the antibacterial and biofilm eradicating efficiency of rifampicin against MRSA and also reduced the formation of persisters. Thus, the present study revealed the sarA dependent antibiofilm efficacy of MRSA and suggests thymol as the promising combinatorial candidate in potentiating the antibacterial activity of rifampicin against persistent MRSA infections.